The Relationship with Western Civilization in the Thought of Malek Bennabi - Boumenjel, Abdelmalek (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2022)
This article deals with the topic of the relationship with Western civilization in the thought of Malek Bennabi in terms of his own relationship with this civilization, as well as the nation’s relationship with it, from his perspective. The binary view of repulsion or attraction was dominant in religious, intellectual, and cultural circles. This article is a summary of Bennabi’s philosophy on the subject, extricated from his writings. It consists of two parts: The first relates to the crux of Bennabi’s answer to the question of the relationship with Western civilization, including his scientific analysis of its ascent, his objective position towards it, and his detection of the systematic flaws in construing it. The second part discusses the post-Bennabi development of the issue of the relationship with Western civilization, with a brief reference to the position of both Roger Garaudy and Taha Abdel Rahman.